Synthesis and characterization of high-performance supercapacitor devices based on carbon/MnO2 composite and carbonized iron cations adsorbed onto polyaniline/nickel graphene foam - Manyala, Ncholu I. (University of Pretoria, 2021)
Thesis (PhD (Physics))--University of Pretoria, 2020.